Relationship between two non-expansive tests of the anaerobic threshold with the endurance performance of athletes practicing - Boufadene, othmane (sports creativity, 2025)
The study aims to Knowing the relationship between non-expansive tests for the anaerobic threshold with the endurance performance of athletes practicing, when we followed the descriptive approach, and the study sample reached 24 male athletes whose ages ranged(23-25 years)who were chosen intentionally, each athlete performed two running tests for anaerobic threshold estimation; the first test (TEST VDOT) (400m-800m) and the second test (TEST BAS) (3000m-2000m) and a 5000m endurance test; main results show that the two anaerobic threshold tests correlated negatively with the 5000m endurance test; and the 5000m endurance performance is more closely associated with (VDOT TEST) than (BAS TEST ) , Thus the (VDOT TEST) is the most precise non-invasive test to estimate the anaerobic threshold